Effect of thickness on the electrical and optical properties of Sb doped SnO2 (ATO) thin films - Giraldi, T. R.; Escote, M. T.; Bernardi, MIB; Bouquet, V; Leite, E. R.; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Kluwer Academic Publ, 2004)
This work reports the preparation and characterization of (SnO2) thin films doped with 7 mol% Sb2O3. The films were prepared by the polymeric precursor method, and deposited by spin-coating, all of them were deposited on amorphous silica substrate. Then, we have studied the thickness effect on the microstrutural, optical and electric properties of these samples. The microstructural characterization was carried out by X-ray diffraction (XRD) and scanning tunneling microscopy (STM). The electrical resistivity measurements were obtained by the van der Pauw four-probe method. UV-visible spectroscopy and ellipsometry were carried out for the optical characterization. The films present nanometric grains in the order of 13 nm, and low roughness. The electrical resistivity decreased with the increase of the film thickness and the smallest measured value was 6.5 x 10(-3) Omega cm for the 988 nm thick film. The samples displayed a high transmittance value of 80% in the visible region. The obtained results show that the polymeric precursor method is effective for the TCOs manufacturing.
Keywords: thin film; tin oxide; antimony